BIOLOGY AND FOOD UTILIZATION EFFICIENCY OF PERICALLIA RICINI (FAB.) (LEPIDOPTERA : ARCTIIDAE) IN TRIPURA - GHOSH, D.; GONCHAUDHURI, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Bilogy of Pericalliaricini on fresh leaves of Ricinus communis was observed in the laboratory at a temperature, ranging from 23 -30°C. Duration and basic features of each developmental stage were noted. Entire life cycle was completed in 35-38 days. Results of food utilization efficiency showed that consumption, egestion, assimilation and production increased with the progressive instars. The consumption index was highestin the secondinstar, growth rate in the 1st instar, assimilation efficiency in the 4th instar. Both gross production efficiency and net production efficiency was highest in the first instar.